2009
DOI: 10.1016/j.jpainsymman.2007.12.023
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Pilot Study to Evaluate Use of Intravenous Lidocaine for Opioid-Refractory Pain in Cancer Patients

Abstract: Opioid-refractory pain is distressing because it is notoriously difficult to treat. Relief from adjuvant therapies often occurs after a lag time. Retrospective evidence points to a role for intravenous (IV) lidocaine in this setting for pain relief. This study was planned as a randomized, double-blind, placebo-controlled, crossover study in which eligible patients received both lidocaine and placebo infusions separated by two weeks. Primary endpoints were magnitude and duration of pain relief. Fifty patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 18 publications
2
48
0
3
Order By: Relevance
“…In keeping with Sharma et al [3], we describe a case in which refractory cancer pain was effectively treated with intravenous lidocaine, exhibiting early analgesic response during infusion. Furthermore, the prolonged analgesic effect of lidocaine was pivotal in achieving the patient's wish of care being delivered at home through the provision of sustained pain relief at the end-of-life.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In keeping with Sharma et al [3], we describe a case in which refractory cancer pain was effectively treated with intravenous lidocaine, exhibiting early analgesic response during infusion. Furthermore, the prolonged analgesic effect of lidocaine was pivotal in achieving the patient's wish of care being delivered at home through the provision of sustained pain relief at the end-of-life.…”
Section: Discussionsupporting
confidence: 70%
“…Systemic delivery of lidocaine has been used for analgesic effect for many years, and both intravenous and subcutaneous delivery have been utilised in the palliative setting [1,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the intravenous administration of lidocaine, another sodium channel blocker, can produce long-lasting analgesia. In cancer patients with opioid-refractory pain, mean duration of analgesia was 9.3 ± 2.6 days after a single infusion 18 . For intractably painful diabetic neuropathy, intensity of pain was diminished for up to 28 days after an infusion 19 .…”
Section: Discussionmentioning
confidence: 99%
“…One study in patients with cancer with refractory pain showed improved analgesia with a single dose of lidocaine. 165 The recommended starting dose is 1 to 5 mg/kg infused for 20 to 30 minutes. In patients who are frail, lower doses may be needed.…”
Section: Oral and Parenteral Local Anestheticsmentioning
confidence: 99%